Reconhecimento de cônicas via diagonalização de matrizes - Gama, Suely Silva Santos (2016)
This thesis will make a study of the conic, which can be defined as quadratic equations solutions with two variables, with the main objective recognition of same through a simplification of the quadratic form associated, whose procedure involves the diagonalization of symmetric matrices. Throughout this work, will address the prerequisites needed for the reader with little familiarity on the subject, can understand each stage of its development, as Euclidean spaces and matrix diagonalization.